The Cultural Survival of Traditional Islamic Education: Dayah Ulee Titi in Modern Aceh, Indonesia - Sabirin Sabirin; Mohamad Yusuf; Irwan Abdullah; Mujiburrahman Mujiburrahman; Zaenuddin Hudi Prasojo (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
Studies of traditional Islamic educational institutions have tended to show these institutions playing a less prominent social role as society has modernized. This research seeks to show a different phenomenon, namely one in which a traditional Islamic educational institution (dayah) has been able to endure and maintain its important role in society. The socio-cultural dynamics of Aceh have had a contribution to the continued existence of the dayah in the new media era. Analysis shows that, even as other traditional educational institutions have been marginalized, Dayah Ulee Titi has grown significantly. It recommends a more in-depth study into the dynamic relationship between traditionalism and modernism to explore how the two co-exist in the field of education.